INCOME DIVERSIFICATION OF ESTATE SECTOR IN SRI LANKA - Dharmadasa, R.A.P.I.S.; Polkotuwa, P.W.T.P. (University of Jaffna, 2016)
This study aims to identifying determinants of income diversification at household level in Sri Lankan estate sector. Analysis builds on data of Household Income and Expenditure Survey 2009/2010 conducted by Department of Census and Statistics of Sri Lanka. The data set covered 1736 households in Sri Lankan estate sector. Herfindhal Index was applied to calculate income diversification at household level and Censored Tobit model was used to identify the determinants of income diversification. The econometric analysis shows that gender and age of the household head, household size, ownership of agricultural land, number of workers above 15 years old and availability of migrants in a household have significantly contributed to the performance of income diversification. Further study indicates that migrants of estate household play a critical role in non estate income. All in all, the study clearly depicts that income diversification has become one of the important strategies of income improvement in estate households
Keywords: Income; Diversification; Households